Overview of the Clean Sky 2 Technology Evaluator Project Methodology - Alf Junior; Alexandra Leipold; Marc C. Gelhausen (Aerospace)
Clean Sky 2 (CS2) was established to reduce the environmental impact of air transport by the introduction of new advanced aeronautical technologies, to improve mobility and to demonstrate reduction potentials for CO2, NOx, and noise emissions of from 20% to 30% as compared to state-of-the-art aircraft in 2014. A wide range of new technologies has been integrated into vehicle performance models for a set of concept aircraft, and the Clean Sky 2 Technology Evaluator (TE) has performed assessments with three major pillars: Vehicle- or mission-level reference aircraft, reflecting 2014 technologies, are compared with new Clean Sky 2 concept aircraft with a focus on CO2 and NOx emission and noise reduction potentials. At the airport level, environmental impact assessments for different traffic and fleet mixes are carried out, namely, noise on the ground and population impacted by certain noise levels and emissions (CO2 and NOx). At the level of the global air transport system (ATS), those new concept aircraft are embedded in fleet projections until 2050 and compared to a projection without new Clean Sky 2 aircraft to understand the emission reduction potentials of future global fleets and the long-term aviation footprint. This paper gives a conceptual overview of the work carried out in Clean Sky 2.